2019
DOI: 10.37898/spc.2019.4.3.083
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Marital Satisfaction and Life Satisfaction with Spiritual Orientation: The Mediating Role of Sacrifice and Sensitivity

Abstract: The purpose of this research is to test the proposed structural model related to the mediating role of sensitivity and sacrifice on the relationship of marital satisfaction and life satisfaction with married individuals’ spiritual orientations. The research has been performed with a total of 454 married individuals living in Turkey, of which 280 (61.7%) are females and 174 (38.3%) are males. The Relationship Happiness Questionnaire, Satisfaction with Life Scale, Spiritual Orientation Scale, Sensitivity Scale, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 41 publications
0
4
0
1
Order By: Relevance
“…However, it is expected that women will be more influenced by social relations, according to what the study of Winterbrook (2017) indicated. The study of Sayin et al (2019) showed that happily married men expressed a higher level of satisfaction with the achievement of life goals, which indicates that social relations were considered the highest level of achievement of life goals for men and women.…”
Section: -Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, it is expected that women will be more influenced by social relations, according to what the study of Winterbrook (2017) indicated. The study of Sayin et al (2019) showed that happily married men expressed a higher level of satisfaction with the achievement of life goals, which indicates that social relations were considered the highest level of achievement of life goals for men and women.…”
Section: -Discussionmentioning
confidence: 99%
“…A qualitative analysis demonstrated that religiosity and spiritual well-being do not significantly impact life satisfaction or life goals (Sayin et al, 2019). The findings from a conducted survey showed that although many individuals were committed to religion and attended a worship house often, they did not have a high satisfaction level in their lives (Lim & Putnam, 2010).…”
Section: -2-the Difference In the Level Of Importance Of The Life Gomentioning
confidence: 98%
See 2 more Smart Citations
“…Bu durum, bazı bireylerin bu tür hizmetleri aramalarını veya kabul etmelerini engelleyebilir (Jones & Butman, 1991). Ayrıca, dinsel inançları olmayan veya farklı dinsel inançlara sahip bireyler için bu hizmetlerin uygunluğu sorgulanabilir (Richards & Bergin, 2000). Kilise merkezli aile manevi danışmanlık ve rehberliğinin geleceği, bu hizmetlerin daha kapsayıcı ve çeşitli hale getirilmesiyle daha da parlak olabilir.…”
Section: Aile çAlışmalarında Manevi Danışmanlık Ve Rehberlik Hizmetleriunclassified